Soil and agronomic factors influencing fodder production in the sub-humid zone of West Africa - Ahmad, N. (International Livestock Centre for Africa, 1986)
Examines the traditional farming in the sub-humid zone of West Africa, the environment and its relationship to agriculture, maintainance of soil fertility including scale of problems and cultural & indigenous methods, pasture agronomy research in northern Nigeria including ILCA's and NAPRI's programmes, and the appropriateness of the two programs. Outlines research needs, and research facilities at ILCA, Kaduna. Ends with suggestions for the modifications of the ILCA program at Kaduna and to conduct the proposed studies, and implications for centre facilities.